Factors influencing healthcare workers’ perceived compliance with infection prevention and control standards, North Bank East region, The Gambia, a cross-sectional study - Sheriffo M.K. Darboe; Sandra A. Darfour-Oduro; Godsway Edem Kpene; Abou Kebbeh; Nuha Fofana; Manjally Ndow; Kawsu Sanyang; Dwomoh Duah; Alfred Edwin Yawson; Ernest Kenu; Harriet Affran Bonful (BMC Research Notes)
Abstract Background This study evaluated Health Care Workers’ (HCWs) knowledge, attitude, perceived compliance, and potential influencing factors related to Infection Prevention and Control (IPC) standards in the North Bank East region of The Gambia. Method The study was an analytic cross-sectional study, conducted in 2021 using a multistage sampling technique. Thirteen health facilities were sampled from the North Bank East Region of The Gambia. The sample size was calculated using the Cochrane formula, based on a healthcare worker population of 408, with a 95% confidence interval. Adjustments were made for a 10% non-response rate and a compliance level of 50%. A final sample size of 218 was used for the study. Descriptive statistics, chi-square, and logistic regression were done at a 95% confidence limit and an alpha level of 0.05. A p-value of 0.05 was considered statistically significant. Results Among the 218 healthcare workers, the majority demonstrated adequate knowledge (86.24%) and a positive attitude (78.4%) toward Infection Prevention and Control (IPC). About half (50.5%) of the HCWs did not comply with IPC standards. Good attitude of HCWs [aOR = 3.13, 95%CI: 1.17–8.41, p-value = 0.023], accessibility of Personal Protective Equipment [aOR = 2.34, 95%CI: 1.01–5.38; p-value = 0.046], and monitoring of IPC practice [aOR = 3.95, 95%CI: 1.84–8.45; p-value = < 0.001] were independently associated with HCWs perceived compliance with IPC standards. Conclusion Although 188 (86.24%) HCWs displayed adequate knowledge of IPC standards, perceived compliance remains insufficient in Gambian healthcare facilities. To address this, the Ministry of Health should prioritize educational campaigns, and regular training to reinforce HCW knowledge, ensure Personal Protective Equipment (PPE) accessibility, and implement ongoing IPC practice monitoring among healthcare workers.